Single-Polarization and Single-Mode Hybrid Hollow-Core Anti-Resonant Fiber Design at 2 μm - Herschel Herring; Mohammad Al Mahfuz; Md. Selim Habib (IEEE Photonics Journal)
In this paper, to the best of our knowledge, a new type of hollow-core anti-resonant fiber (HC-ARF) design using hybrid silica/high-index material (HIM) cladding is presented for single-polarization, high-birefringence, and endlessly single-mode operation at 2 μm wavelength. We show that the inclusion of a HIM layer in the cladding allows strong suppression of $x-$ polarization, while maintaining low propagation loss and single-mode propagation for $y-$ polarization. The optimized HC-ARF design includes a combination of low propagation loss, high-birefringence, and polarization-extinction ratio (PER) or loss ratio of 0.02 dB/m, 1.2 $× \, 10^{-4}$ , and >550 respectively, while the loss of the $x-$ polarization is >20 dB/m. The proposed fiber may also be coiled to small bend radii while maintaining low bend-loss of $≈$ 0.01–0.1 dB/m, and can potentially be used as polarization filter based on the different gap separations and bend conditions.